Hypofractionated Radiotherapy for Children With Diffuse Intrinsic Pontine Gliomas. Issue 4 (6th November 2015) - Hankinson, Todd C.; Patibandla, Mohana Rao; Green, Adam; Hemenway, Molly; Foreman, Nicholas; Handler, Michael; Liu, Arthur K.
Abstract : Children with diffuse intrinsic pontine gliomas have very poor outcomes, with nearly all children dying from disease. Standard therapy includes 6 weeks of radiation. There have been descriptions of using a shortened course of radiation. We describe our experience with a hypofractionated radiotherapy approach delivered over five treatments. In seven children, hypofractionated radiotherapy was well tolerated, but symptomatic radiation necrosis was seen in three of the children. Overall survival was slightly shorter than previously described in the literature. We are developing a prospective dose‐finding protocol with the goal of tolerable short‐course radiation treatment with outcomes comparable to conventional radiation.